2012
DOI: 10.1074/jbc.m111.272161
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Structural Determinants within Third Intracellular Loop That Direct Signaling Specificity of Type 1 Corticotropin-releasing Hormone Receptor

Abstract: Background: The CRH-R1 is key for mammalian adaptation to stress; however, the structural determinants of signal transduction are unknown.Results: Amino acids identified within CRH-R1 IC3 appear crucial for G protein-dependent cAMP and ERK1/2 signaling.Conclusion: These microdomains provide a tight control of CRH-R1 differential coupling to distinct G proteins and downstream effectors.Significance: This might prevent hyperstimulation of stress-induced responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Residues 5.61 and 5.65 contact the transducin C-terminal peptide in the opsin structures [32], but a larger range of residues contact the G-protein in the β 2 -AR 3SN6 structure. Mutations, particularly to polar amino acids, at position 5.61 and 5.65 in class A [3336] and class B [3739] GPCRs inhibit G-protein coupling. It is important to consider the G-protein interaction when seeking to understand the mutagenesis results for residues at the intracellular end of TM5 Here, the 3SN6 β 2 -AR–G-protein complex is a reasonable model since both CLR and the β 2 -AR couple to Gs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residues 5.61 and 5.65 contact the transducin C-terminal peptide in the opsin structures [32], but a larger range of residues contact the G-protein in the β 2 -AR 3SN6 structure. Mutations, particularly to polar amino acids, at position 5.61 and 5.65 in class A [3336] and class B [3739] GPCRs inhibit G-protein coupling. It is important to consider the G-protein interaction when seeking to understand the mutagenesis results for residues at the intracellular end of TM5 Here, the 3SN6 β 2 -AR–G-protein complex is a reasonable model since both CLR and the β 2 -AR couple to Gs.…”
Section: Resultsmentioning
confidence: 99%
“…The KxxK 6.35 motif may interact with the C-terminus of Gαs, aided by flexing of TM6 around P 6.42 (class B) or P 6.50 (class A). This interaction is born out by MD simulations, but the analogous residues in the β 2 -AR–Gs complex (PDB code 3SN6) are poorly resolved and so the interpretation should be used with care, despite the observations from mutagenesis experiments that implicate K 6.32 and K 6.35 in G-protein coupling in both class A [36,46–48] and class B [39,4952] GPCRs. For this reason, it is important to note that the alignment is based on mutagenesis results throughout the transmembrane region and not in just one region, such as the G-protein coupling region.…”
Section: Resultsmentioning
confidence: 99%
“…CRF 1 and CRF 2 receptors are class B1 (secretin-like) GPCRs with complex signaling mechanisms that can couple to different G proteins in a cell-type-specific manner to produce an array of downstream signaling. Although both receptors are reported to activate Gas and cAMP signaling and Gq and Ca 2+ signaling [56,57], there is also clear evidence for coupling to Gq/11 and Gi/o proteins [30,[58][59][60]. The latter 2 contribute to activating ERK [58,61].…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, using flash photolysis, Franke et al (59) demonstrated that a mutation of K248 in IL3 of rhodopsin did not affect G‐protein (transducin) binding but impaired G‐protein activation. Since this early report, other studies have shown the importance of IL3 in G‐protein binding and activation, including a recent report on the corticotropin‐releasing hormone receptor that showed the importance of several arginine and lysine residues in this domain in the activation of G‐proteinmediated signaling cascades (60). Although an increasing number of studies have implicated arginine residues in ILs as important for GPCR signaling, no consensus sequence for G‐protein coupling has been identified, likely due to the high sequence diversity within these loops among GPCRs.…”
Section: Discussionmentioning
confidence: 99%